CROSS-BORDER PAYMENT DIGITALIZATION: THE PHENOMENON OF QRIS ACCEPTANCE IN MALAYSIA FROM THE PERSPECTIVE OF THE DIGITAL ECONOMY AND MSME EMPOWERMENT - Andi Hasyriningsih Asfar; Siti Fatonah; Malik Fatoni; Surti Zahra; Didi Wandi; Hendry Gunawan (Amal Insani Foundation, 2026)
This study aims to analyze a unique phenomenon identified during an international community service activity in Malaysia, namely the refusal of cash payments in Indonesian rupiah and Singapore dollars in several souvenir shops, while digital payments based on QRIS were accepted. This phenomenon is noteworthy as it reflects a shift in cross-border transaction practices from conventional systems toward regionally integrated digital payment systems. The study employs a descriptive qualitative approach through field observation and a literature review related to payment connectivity between Bank Indonesia and Bank Negara Malaysia. The analysis focuses on the implications of digital economy development for transaction efficiency and MSME empowerment. The findings indicate that cross-border QR code interoperability not only enhances transaction efficiency and convenience but also strengthens financial inclusion and ASEAN economic integration. These results suggest that payment digitalization has the potential to become a new model of technology-based economic integration in Southeast Asia. This study provides a contemporary perspective on the transformation of cross-border payment systems and opens further discussion on the future of the regional digital economy.